(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
Epilepsy is one of the major neurological disorders occurring due to the abnormal functioning of the various receptors and enzymes in the central nervous system. Many potentials drugs were developed in recent times which act on ion channels like sodium (Na+), calcium (Ca2+), chloride (Cl-), and receptors like GABA receptor and enzymes like GABA transaminase. Some drugs act as enzyme, ion channel inhibitors or blockers, and some drugs as receptor agonist like barbiturates, benzodiazepines acting on GABA receptors. In the present study performed computational techniques in order to develop better inhibitors for the enzyme GABA transaminase by modifying the terminal ‘methyl’ group of the Valproic acid structure with electrophilic, nucleophile and neutral pharmacophoric features. Molecular mechanics studies has been carried out for the analogs and protein – ligand interactions of these analogs was identified through docking studies using GOLD 4.1 software against the enzyme 4-aminobutyrate-aminotransferase(GABA transaminase). From the docking studies we found that replacement of methyl with amine, hydrogen and hydroxyl groups (hydrophilic groups), are showing better fitness than that of the valproic acid.